2011
DOI: 10.1021/jm101165z
|View full text |Cite
|
Sign up to set email alerts
|

A Class of 5-Benzylidene-2-phenylthiazolinones with High Potency as Direct 5-Lipoxygenase Inhibitors

Abstract: A novel class of potent direct 5-lipoxygenase (5-LO) inhibitors bearing a thiazolinone-scaffold identified by virtual screening is presented. A range of substitutions and the importance of the 2-phenyl moiety were evaluated. This series is characterized by high potency in intact polymorphonuclear leukocytes and a cell-free system, exemplified by (Z)-2-(4-chlorophenyl)-5-(4-methoxybenzylidene)-5H-thiazol-4-one (18, IC(50) = 0.28 and 0.09 μM). These disubstituted thiazolinones may possess potential for intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…It is categorized as an iron ligand inhibitor that also shows redox activity [9]. YS121 and CAY10649 are predicted to be non-redox inhibitors, based on their structures and functional moieties [13], [14]. Caffeic acid and its derivative, CDC, are redox inhibitors, according to a radical scavenging assay [15].…”
Section: Methodsmentioning
confidence: 99%
“…It is categorized as an iron ligand inhibitor that also shows redox activity [9]. YS121 and CAY10649 are predicted to be non-redox inhibitors, based on their structures and functional moieties [13], [14]. Caffeic acid and its derivative, CDC, are redox inhibitors, according to a radical scavenging assay [15].…”
Section: Methodsmentioning
confidence: 99%
“…This set and the experimental activities were extracted from two studies performed by the same research group [9,10]. The IC 50 values (concentration of a compound required to inhibit 50% of the 5-LOX activity) exhibit a range of activity from 60 to 11,000 nM.…”
Section: Data Setmentioning
confidence: 99%
“…1 [8]. With the aim of finding new drugs that present fewer adverse effects than Zileuton, many 5-LOX inhibitors have been designed and synthesized in the recent years [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, Schneider and co-workers demonstrated that single round of pharmacophore-based compound ranking is insufficient to identify potent hits and a multistep virtual screening procedure methods including structure based similarity searching is more accurate and productive in retrieving new scaffolds and potential 5-LOX inhibitors. One of the hits obtained from the study, Mol-19 was further employed for scaffold hopping and a novel potential inhibitor of 5-LOX, Mol-20 (IC 50 of 0.09 µM) was developed and the study has been recently published [150]. …”
Section: Application Of Lbdd In 5-lox Inhibitor Developmentmentioning
confidence: 99%